Primary Education in Southeast Asia: A Comparative Analysis between Indonesia and Philippines School Curriculum - Aulia Ihza Cahya; Elizar Elizar; Badawi Badawi; Masitoh Masitoh; Meutia Rachmatia; Berta Apriza (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study aims to compare the implementation of elementary curricula in the Philippines and Indonesia, focusing on ten key aspects: Curriculum Function, Curriculum Vision, Aims and Objectives, Values and Principles, Philosophy of Teaching and Learning, Curriculum Architecture, The Importance of Competency, Areas of Learning, Teaching Methodology and Strategies, and Assessment. The objective is to describe and analyze the differences between the curricula of these two countries. A qualitative approach with a multi-site case study design was employed, involving elementary schools in both Indonesia and the Philippines. Data collection methods included surveys, in-depth interviews with staff from six schools in each country, lesson observations, and document analysis. Informants were selected using purposive sampling to ensure the inclusion of experienced individuals from the Education office, school principals, and teachers, totaling 12 informants from both Indonesia and the Philippines. The findings reveal notable differences in the curricula across the ten aspects studied. The Indonesian education curriculum emphasizes the development of character, morals, and social skills, whereas the Philippine education curriculum prioritizes the enhancement of students' cognitive abilities.